2015
DOI: 10.1515/sem-2014-0079
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the unconscious mind of the consumer: How implicit attitudes predict pre-conscious visual attention to carbon footprint information on products

Abstract: Consumers clearly have a role to play in the global fight against climate change since even relatively small changes in patterns of household consumption could significantly reduce greenhouse gas emissions. But what evidence is there that consumers do consider the environmental impacts of products when shopping? Indeed, how psychologically salient are the carbon footprint labels now appearing on a range of products in various countries?Here we test the psychological salience of this information using eye-track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Eye movements are proxies of attention and the acquisition of information (Wedel & Pieters, 2008). A few eye-tracking studies investigate attention to labels that signal the environmental sustainability of products (Beattie & McGuire, 2015;Beattie, McGuire, & Sale, 2010;Samant & Seo, 2016;Van Loo et al, 2015), suggesting that understanding of an importance assigned to sustainability labels lead to higher attention (Samant & Seo, 2016;Van Loo et al, 2015). In the restaurant menu context, a few studies investigated how restaurant customers read menus using eye-tracking (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Eye movements are proxies of attention and the acquisition of information (Wedel & Pieters, 2008). A few eye-tracking studies investigate attention to labels that signal the environmental sustainability of products (Beattie & McGuire, 2015;Beattie, McGuire, & Sale, 2010;Samant & Seo, 2016;Van Loo et al, 2015), suggesting that understanding of an importance assigned to sustainability labels lead to higher attention (Samant & Seo, 2016;Van Loo et al, 2015). In the restaurant menu context, a few studies investigated how restaurant customers read menus using eye-tracking (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Spence, Poortinga, Butler, & Pidgeon, 2011) and their agreement with pro-environmental attitudes. Beattie and Sale (2009) reported about 70 percent of surveyed individuals expressed a preference for low carbon products recognized by carbon footprint information on product labels. In addition, the resistance to more sustainable behavior is not attributable to insufficient knowledge about climate change (Pidgeon, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has identified an intention-behaviour gap when considering the adoption of sustainable behaviour (Bamberg 2003). It has been hypothesised in the past that this gap may be due to a dissociation between explicit and implicit attitude -explicit self-report attitudes to the environment may be positive, but underlying implicit attitudes may not, and these implicit attitudes may be more influential for guiding certain aspects of behaviour (Beattie 2010;Beattie and McGuire 2015). However, as participants appeared to report this contradiction by explicitly scoring their environmental behaviour as lower than environmental concern, it could also be explained by a lack of awareness of how to act in a sustainable way.…”
Section: Discussionmentioning
confidence: 99%
“…However, carbon labelling clearly does need to be simple (such as the traffic signal approach) to have the desired effect in the time frame required for supermarket shopping. Carbon labelling that is not simple does not seem to attract the visual attention of consumers in that very short time frame, (Beattie 2012b), except for those with the necessary very positive implicit attitude (Beattie and McGuire 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation